Unmasking the black science boxes: an analysis of speech and jargons used by students of scientific initiation - Silva, Rodrigo Régis Campos; Calefi, Paulo Sérgio; Coutinho, Francisco Ângelo (Revista Hipótese, 2017)
In this article, we apply the theories of Bruno Latour and collaborators in the analysis of the language used by students of scientific initiation of a specific area of knowledge of chemistry, with the objective of finding the controversies and uncertainties of the scientific practice, through the use of expressions widely used but not always understood. We also analyze the discourse of these students, using the classification of the types of statements of scientific discourses, elaborated by Bruno Latour and Steve Woolgar. We corroborate with the ethnography within the research laboratories, made by the same, that criticizes the lack of contradiction of scientific discourse and explains the use of various jargon by the influence of external literature to the laboratory and by the imposition of writing texts in scientific language.
Keywords: Scientific Initiation; Bruno Latour; Scientific Practice